2021
DOI: 10.3390/ijms22105304
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Study of Drug Resistance Mutations in HIV-1 Infected Individuals under Antiretroviral Therapy in Brazil

Abstract: The success of antiretroviral treatment (ART) is threatened by the emergence of drug resistance mutations (DRM). Since Brazil presents the largest number of people living with HIV (PLWH) in South America we aimed at understanding the dynamics of DRM in this country. We analyzed a total of 20,226 HIV-1 sequences collected from PLWH undergoing ART between 2008–2017. Results show a mild decline of DRM over the years but an increase of the K65R reverse transcriptase mutation from 2.23% to 12.11%. This increase gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
(111 reference statements)
1
4
0
Order By: Relevance
“…According to the 2022 International Antiviral Society (IAS)‐USA Drug Resistance Mutation Update, the magnitude of the reduction in susceptibility varies considerably, with those defined as major mutations most closely related to premature treatment failure and associated with significant reductions in susceptibility [8]. Our finding of high prevalence of K103N is similar to other studies [5, 10–12]. Among the participants in this study with E138A/G/K/Q mutations, all of them had subtype B.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to the 2022 International Antiviral Society (IAS)‐USA Drug Resistance Mutation Update, the magnitude of the reduction in susceptibility varies considerably, with those defined as major mutations most closely related to premature treatment failure and associated with significant reductions in susceptibility [8]. Our finding of high prevalence of K103N is similar to other studies [5, 10–12]. Among the participants in this study with E138A/G/K/Q mutations, all of them had subtype B.…”
Section: Discussionsupporting
confidence: 80%
“…studies [5,[10][11][12]. Among the participants in this study with E138A/G/K/Q mutations, all of them had subtype B.…”
Section: Discussionmentioning
confidence: 89%
“…However, several downsides have emerged or remain critical: (i) the therapy is lifelong; (ii) the oral route is the only path of administration, leading to issues for patients with dysphagia or altered consciousness; (iii) all available compounds need to be taken daily, which requires high compliance by the patient; (iv) the aging of the HIV-population also leads to age-related pathologies (e.g., dementia) [9][10][11]; (v) polypharmacotherapy must account for the risk of incorrect drug assumption and interaction [12]; (vi) there are still patients with limited treatment options due to viral resistance for those in whom preserving available molecules remains critical [13,14]; and (vii) the current SARS-CoV-2 pandemic has led to a more complex and discontinued retention in care and treatment adherence [15]. Currently, clinicians should evaluate all the previously described characteristics to prescribe the perfect treatment for each person.…”
Section: Introductionmentioning
confidence: 99%
“…As transmitted or acquired DRMs constitute significant risk factors for ART effectiveness and AIDS therapy (Günthard et al, 2019;Li et al, 2021), HIV genotypic resistance testing has been advised for ART initiation, failure, and modification (Department of Health and Human Services, 2020). The development of DRM is a serious danger to the ongoing management of HIV replication as well as the possibly associated rise in viral strain transmission, which could increase the incidence of TDR (Tanaka et al, 2019;Santos-Pereira et al, 2021). In 2021, WHO recommended DTG combination with an NRTI backbone as the preferred regimen for PLHIV-infected individuals initiating ART (World Health Organization, 2021a).Many studies (Rocheleau et al, 2018;Crowell et al, 2021;Hackett et al, 2021;World Health Organization, 2021b) have shown that both NNRTIs and NRTIs induce high levels of HIV drug resistance among individuals with treatment failure (VL>1000 copies/ml), which collectively corroborate our results.…”
Section: Discussionmentioning
confidence: 99%